«Вельможа» Крылова: Жанр, источники, датировка [Krylov’s “Vel’mozha”: Genre. Sources. Dating] - Liamina, Ekaterina; Samover, Natalia (Slavica Revalensia, 2022)
This pioneering article-length study of Ivan Krylov’s last fable “Vel’mozha” (“Grand Seigneur”) addresses the text’s central character (there are serious reasons to assume that the grand seigneur represents Chancelor Viktor Kotchubey), and examines the fable’s pragmatics, involved allusions, and genre. It also puts forth a likely new date of the “Grand Seigneur’s” composition — 1834.